Comparison of ovulation induction treatments in intrauterine insemination; A retrospective study in a tertiary center (Annals of Medical Research, 2021)
Aim: In this study, were compared of different ovarian stimulation drugs used in intrauterine insemination ( IUI) cycles. Material and Methods: The records of 3420 infertile patients who presented to the outpatient clinic were retrospectively analyzed. The patients were evaluated into three groups ( n=421). 170 patients who received letrozole treatment were included in group 1, 50 patients who received Clomiphene citrate (CC) treatment were included in group 2, and 201 patients who received gonadotropins treatment were included in group 3.Results: The mean numbers of follicles were in IUI cycles stimulated with the use of letrozole (1.5± 0.6), CC (1.6 ± 0.6), and gonadotropins (1.6 ± 0.7). After stimulation with letrozole, CC and gonadotropins, pregnancy rates were 13(7.6%), 6(12%) and 19(9.4%); Abortion rates were 2(1.1%), 1(2%) and 3(1.4%). Multiple pregnancy occurred in, 1/170 (0.58%), 1/50 (2%) and 2/201 (0.99%) in the letrozole, CC and gonadotropins groups.Conclusion: After stimulation with treatment protocols; pregnancy rates, abortion rates, and multiple pregnancy rates were similar.The question that this study set out to answer was of effectiveness. Different ovarian stimulation protocols used in IUI programs, clinical opportunities, experience of the person, does affect the results of the study.
Keywords: Clomiphene citrate; gonadotropins; intrauterine insemination; letrozole; ovulation induction